The effect of teaching Arabic grammar according to functional education in the achievement of female students fourth grade literary - Al-Husseini, Lecture.Wesal Muayyad Khudair (Thi Qar Arts Journal, 2022)
The issue of the weakness of female students in Arabic grammar is an obstacle that was and still exists, despite the large number of scientific studies that dealt with this phenomenon and tried to reduce it, but it still exists to this day. The importance of Arabic language stems from its being the most important link between individuals and groups, and therefore nations are interested in teaching their languages because it is a tool for thinking and expression, and it is a tool of understanding and communication between man and his environment. It is compatible with the students’ perceptions and understanding, and the experience and knowledge that they are equipped with. Arabic language is an honorable language of great stature that no language in the world has reached, neither in its past, nor in its present, nor in its future, because God Almighty revealed through it the Noble Qur’an that came to all mankind. Arabic language grammar is of great importance because it is the faithful fortress, as it protects the tongue from melody and works to straighten the students’ tongues, accustom them to accuracy and to the correct use of words and structures, train them to think continuously, and enable them to understand complex and ambiguous structures. As for the importance of the functional method in teaching Arabic grammar, because it aims to address grammatical rules in educational situations, and targets the aspect of meaning and the linking of words to each other when performing their meanings. The importance of grammatical rules and their distinct status is what prompts us to teach them in ways that appeal to requests, and the method of teaching is one of the most important problems of teaching Arabic grammar. Keywords: Arabic Grammar, teaching, language, functional, method